2019
DOI: 10.1099/jgv.0.001294
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing I292V PB2 mutation in avian influenza H9N2 virus increases viral polymerase function and attenuates IFN-β induction in human cells

Abstract: Adaptation of PB2 protein is important for the establishment of avian influenza viruses in mammalian hosts. Here, we identify I292V as the prevalent mutation in PB2 of circulating avian H9N2 and pandemic H1N1 viruses. The same dominant PB2 mutation is also found in most human isolates of emergent avian H7N9 and H10N8 viruses. In human cells, PB2-292V in H9N2 virus has the combined ability of conferring higher viral polymerase activity and stronger attenuation of IFN-β induction than that of its predecessor PB2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Several residues in the PB2 protein have been previously identified as virulence markers as well as factors contributing to interspecies transmission of influenza A viruses in mammals (39,(46)(47)(48)(49). In particular, some mutations, such as E627K, D701N, E158R, A271T, Q591R, H357N, T558I, K339T, A588T, I147T, and I292V (46,47,(50)(51)(52)(53)(54)(55)(56), in the PB2 protein are essential to determine the pathogenesis of influenza viruses in mammals. In this study, we first demonstrated that the PB2 protein had a major effect on the viral pathogenicity of two H1N1 SIVs, with the other genes playing only minor roles in virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Several residues in the PB2 protein have been previously identified as virulence markers as well as factors contributing to interspecies transmission of influenza A viruses in mammals (39,(46)(47)(48)(49). In particular, some mutations, such as E627K, D701N, E158R, A271T, Q591R, H357N, T558I, K339T, A588T, I147T, and I292V (46,47,(50)(51)(52)(53)(54)(55)(56), in the PB2 protein are essential to determine the pathogenesis of influenza viruses in mammals. In this study, we first demonstrated that the PB2 protein had a major effect on the viral pathogenicity of two H1N1 SIVs, with the other genes playing only minor roles in virulence.…”
Section: Discussionmentioning
confidence: 99%
“…We have listed and analyzed the potential virulence determinants in the HA, NA, PB2 and NS1 genes of the two viruses in Table S3. Among these mutations, I292V and A588V in PB2 genes have been reported associated with increased polymerase activity in mammalian and/or avian cell line and increased virulence in mice [49,50]. The two mutations were observed in GS38 virus but not DK09 virus, which might contribute to the difference of the mean death time.…”
Section: Discussionmentioning
confidence: 97%
“…An obvious shortcoming here is that we did not measure IFN-β expression in different cell cultures after the infection with different H5N8/H9N2 reassortants to elucidate the role of PB2 and PA in the inhibition of IFN-response ( Hayashi, MacDonald, and Takimoto 2015a ; Gao et al. 2019 ) or to quantify IFN-β levels in different cells ( Hsu et al.…”
Section: Discussionmentioning
confidence: 99%
“…2010 ; Zhao et al. 2014 ; Hayashi, MacDonald, and Takimoto 2015a ; Gao et al. 2019 ), and synergism with NS1 is required for efficient virus replication in vivo and in vitro ( Varga et al.…”
Section: Discussionmentioning
confidence: 99%